2014
DOI: 10.1007/s10517-014-2553-6
|View full text |Cite
|
Sign up to set email alerts
|

Age- and Sex-Related Changes in Heart Rate Variability Under Conditions of Blockade or Stimulation of Peripheral Adrenoceptor in Outbred Rats

Abstract: Changes in heart rhythm variability were studied in male and female mature and 5-6-week-old rats under conditions of 7-day administration of β1-adrenoreceptor blocker atenolol (2.5 mg/kg) and α1-adrenoreceptor agonist phenylephrine (0.3 mg/kg). Atenolol administration to mature rats was followed by a slight deceleration of cardiac rhythm, a tendency to heart rate variability decrease in the HF range, and moderate increase in centralization of regulation. In 6-week-old rats, increased variability of cardiointer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…However, there are several studies demonstrating the impact of different autonomic and non-autonomic factors on HRV, which could be associated with DOX-induced cardiotoxicity. Concerning autonomic factors, modulation of autonomic nervous activity to the heart, adrenoceptor (AR) and muscarinic receptor density [59, 60], their function [46] and AR receptor activated intracellular signaling pathways [46,61] are proposed while suggested non-autonomic factors mainly include inflammation [62,63] and oxidative stress [46,63,64]. Based on the reports of the above-mentioned studies, some potential mechanisms underlying the HRV modulation in DOX-induced cardiotoxicity observed in the present research might be proposed.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are several studies demonstrating the impact of different autonomic and non-autonomic factors on HRV, which could be associated with DOX-induced cardiotoxicity. Concerning autonomic factors, modulation of autonomic nervous activity to the heart, adrenoceptor (AR) and muscarinic receptor density [59, 60], their function [46] and AR receptor activated intracellular signaling pathways [46,61] are proposed while suggested non-autonomic factors mainly include inflammation [62,63] and oxidative stress [46,63,64]. Based on the reports of the above-mentioned studies, some potential mechanisms underlying the HRV modulation in DOX-induced cardiotoxicity observed in the present research might be proposed.…”
Section: Discussionmentioning
confidence: 99%
“…The 19 studies listed in Table 2 met the review criteria, and quality appraisal of these studies is outlined in Supplemental Digital Content 3, Supplemental Table S3, http://links.lww.com/JCN/A212. Of these manuscripts, 11 were human HRV studies [17][18][19][20][21][22][23][24][25][26][27] and 8 were preclinical rodent HRV studies [28][29][30][31][32][33][34][35] (Table 2). In 18 of the studies, data on adult humans or animals were reported, whereas data on children (median age, 10 years) were reported in 1 study.…”
Section: Resultsmentioning
confidence: 99%
“…In preclinical rodent studies that used b-adrenergic receptors blocking medication (ie, propranolol, atenolol, and metoprolol), pharmacologic SNS blockade was associated with an increase in the mean normal-normal interval (milliseconds) in most studies, 28,[30][31][32]34,35 with the exception of Silva et al, 33 who reported no normalnormal interval change, and Kur'yanova et al, 29 who only reported a change in female rats. In addition, the standard deviation of normal-normal intervals (SDNN) decreased in the 3 animal studies using b-adrenergic receptor blockers who reported this metric.…”
Section: Time Domain Indicesmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Nevertheless, administration of atenolol has been shown to alter HF power with variable responses observed that appear to be age-, sex- or disease-dependent or relate to the duration of atenolol administration. 1619 The exact mechanism by which atenolol changes HF power remains unclear, but may relate to the sympathovagal interactions that are present at the level of the sinoatrial (SA) node. MAP and SBPV were unchanged by atenolol, indicating appropriate compensatory neurohormonal mechanisms were subsequently able to maintain normal BP in the face of a decrease in HR and loss of any β 1 -adrenoceptor-mediated vasodilatory actions.…”
Section: Discussionmentioning
confidence: 99%